Utilizing WhatsApp Translation Strategies for Enhancing Online Interaction in English for Specific Purposes Courses - Sujarwo Sujarwo; Asdar Asdar; Yulini Rinantanti; Akhiruddin Akhiruddin; Sukmawati Sukmawati; Sarmila Sarmila (AL-ISHLAH: Jurnal Pendidikan, 2024)
The integration of instant messaging services into educational settings has become increasingly prevalent, providing unique opportunities for enhanced communication and learning. This study aimed to examine the viewpoints of educators and students regarding the use of instant messaging services, such as WhatsApp, in their translation education and instruction. The study employed a qualitative research approach, specifically content analysis, to examine the utterances of two translation lecturers and fifteen ESP students. The results revealed that participants unanimously agreed that instant messaging services facilitated their teaching and learning of translation by using consistent terminology and rephrasing complex tasks to provide guidance throughout the chat. This approach enriched the translation understanding of ESP students. The study suggests using one consistent term to refer to the translation process throughout the text. In conclusion, chatting applications like WhatsApp are powerful and efficient communication tools that can facilitate an engaging, authentic, and meaningful learning experience when effectively included in English for Specific Purposes (ESP) classrooms for online translation interactions.